The Digital Imaginary Literature and Cinema of the Database - Coover, Roderick (Electronic Literature, 2019)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Over the past half century, computing has profoundly altered the ways stories are imagined and told. Immersive, narrative, and database technologies transform creative practices and hybrid spaces revealing and concealing the most fundamental acts of human invention: making stories. The Digital Imaginary illuminates these changes by bringing leading North American and European writers, artists and scholars, like Sharon Daniel, Stuart Moulthrop, Nick Montfort, Kate Pullinger and Geof Bowker, to engage in discussion about how new forms and structures change the creative process. Through interviews, commentaries and meta-commentaries, this book brings fresh insight into the creative process from differing, disciplinary perspectives, provoking questions for makers and readers about meaning, interpretation and utterance. The Digital Imaginary will be an indispensable volume for anyone seeking to understand the impact of digital technology on contemporary culture, including storymakers, educators, curators, critics, readers and artists, alike.